Miscalculation in Proxy War: The United States and Russia in Syrian Civil War from the Neoclassical Realist Perspective - Osman ŞEN; Mehmet ŞAHİN (Gazi Akademik Bakış)
This article aims to puzzle why the leading military power of the world, namely the United States, was pushed back from the negotiating table in the Syrian Civil War, and conversely, how and why the world’s declining power, namely Russia, became the sole actor in that conflict. The article will try to answer this question from the neoclassical realist perspective. In this perspective, states do not always act rationally. Instead, they can fail because of miscalculations. The United States, in this respect, miscalculated on the Syrian Civil War as well as its domestic politics. In contrast, Russia behaved in accordance with its strategic culture, which resulted in its dominance both in the field and in diplomacy. The systemic stimulus, which is the independent variable, forces both countries to form alliances in the civil war. The domestic actors of both countries, which are the intervening variables, diversified the systemic stimuli in opposite directions. While the US political elite was misguided due to the divided structure, the Russian elite was more unified, which resulted in outcomes in favor of the latter